Respostas
respondido por:
1
Explicação passo-a-passo:
( 4x³ + 2x² — 5x + 3 )(x + 2)
Aplica propriedade chuveirinho:
4x⁴+8x³+2x³+4x²—5x²—10x+3x+6
= 4x⁴+10x³—x²—7x + 6
Espero ter ajudado bastante!)
respondido por:
0
Resposta:
4x⁴+10x³-x²-7x+6
Explicação passo-a-passo:
(4x³+2x²-5x+3) • (x+2) =
=4x⁴+8x³+2x³+4x²-5x²-10x+3x+6
= 4x⁴+(8+2).x³+(4-5).x²+(-10+3).x+6
= 4x⁴+(10).x³+(-1).x²(-7).x+6
=4x⁴+10x³-x²-7x+6
Espero ter ajudado!
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás